Qt 5 blueprints : design, build, and deploy cross-platform GUI projects using the amazingly powerful Qt 5 framework /: design, build, and deploy cross-platform GUI projects using the amazingly powerful Qt 5 framework. (2015) - Huang, Symeon
No abstract available